The correspondence between Matija Mažuranić and his brothers Anton and Ivan, accompanied by a review of Matija’s poem Bĕdna Starost - Ivona Smolčić (Studia Lexicographica)
Matija Mažuranić (Novi Vinodolski, 1817 – Feldhof near Graz, 1881) was a Croatian writer. His literary work Pogled u Bosnu ili Kratak put u onu krajinu (A View of Bosnia, or A Brief Tour of the Other Frontier, 1842) is the first complete travelogue in Croatian literature, notable for dealing with everyday life in Bosnia. The travelogue, which was also of use to Matija’s brother Ivan in writing his own work, Smrt Smail-age Čengića (The Death of Smail-aga Čengić, Iskra, 1846), is distinct because the author did not limit himself to describing what he saw, but rather, imbued the work with his own experience of the region and its inhabitants. In addition, considering that the work was written during the uprising in Bosnia, it also has a socio-political background which falls outside the literary domain. Matija distinguished himself as an avid social worker. Although he was a blacksmith by trade, he engaged in construction work in his hometown and the surrounding area, and even served as the mayor of Novi Vinodolski for some time. He also travelled around Austria, Serbia and Bosnia, and even to Constantinople. The details of his life can be gleaned from the correspondence he kept with his brothers Antun and Ivan Mažuranić, who often helped him financially in the realisation of his business ventures. The letters also reveal the then current social reality and chronicle the events that marked Matija’s travels and life in Novi Vinodolski. Prominent among them were the publication of the translation of The Statute of Vinodol (1843) by Antun Mažuranić and the opening of the National Reading Room (1845) in Novi Vinodolski. Matija’s reflections on his own life path, which complete the impression of him as a man imbued with romantic personality traits, are also worthy of notice. In addition to the above, the paper also reviews Matija’s literary work Bědna starost (Dire Old Age), which is not mentioned in literary historiography, although it is not unknown (Živančević, 1964). It is a ballad that deals with a fictitious tragic event, as a result of God’s will that should be accepted. In addition to romantic features, elements of baroque poetics can be observed in the work, as reflected in centring the themes of human transience, sinfulness, the permanence of the divine, and pessimism.